2017
DOI: 10.1111/nmo.13025
|View full text |Cite
|
Sign up to set email alerts
|

G protein‐coupled estrogen receptor and estrogen receptor ligands regulate colonic motility and visceral pain

Abstract: GPER and ER receptors are involved in the regulation of GI motility and visceral pain. Both may thus constitute an important pharmacological target in the IBS-D therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…There was a correlation between the expression of GPER in patients with IBS-D and the severity of abdominal pain, and an association between the GPER-mediated estrogenic effects on IBS pathogenesis and activation of mast cells in the colon, thus highlighting a novel avenue for understanding the pathogenesis of sex differences in IBS (77). GPER-mediated estrogenic effects were involved in the regulation of visceral pain and GI motility (78).…”
Section: Estrogen and Estrogen Receptors In Intestinal Diseases Irritmentioning
confidence: 99%
“…There was a correlation between the expression of GPER in patients with IBS-D and the severity of abdominal pain, and an association between the GPER-mediated estrogenic effects on IBS pathogenesis and activation of mast cells in the colon, thus highlighting a novel avenue for understanding the pathogenesis of sex differences in IBS (77). GPER-mediated estrogenic effects were involved in the regulation of visceral pain and GI motility (78).…”
Section: Estrogen and Estrogen Receptors In Intestinal Diseases Irritmentioning
confidence: 99%
“…Inflammation would also positively regulate GPER expression, which may add to GPER's neuroprotective effect during postischematic stroke . In addition, GPER activation in the myenteric plexus of the human and rodent colon may lead to decreased colonic motility by promoting NO release from nitrergic nerves …”
Section: What Does Gper Offer To Neuronal Functionmentioning
confidence: 99%
“…In the current issue of Neurogastroenterology and Motility , Zielińska et al. demonstrated that GPER is expressed similarly in the colon and ileum in mice and humans of both genders . The authors also showed both in vitro and in vitro that the GPER agonist (G‐1) inhibited intestinal contractility and significantly prolonged the time to bead expulsion in rats of both genders.…”
Section: Introductionmentioning
confidence: 97%
“…ERs are expressed throughout the brain, including the hypothalamus, amygdala, and midbrain, all of which have been shown to send extensive projections to preganglionic vagal neurons of the DMV, and hence modulate GI functions (12,57,63,80). ERs are also expressed on the myenteric plexus of both rodents and humans (1,58,59,90,93).…”
Section: Estrogen Receptor Signaling and Expressionmentioning
confidence: 99%